Effect of ultraviolet treatment on shelf life of fresh lotus root. Issue 6 (13th April 2020) - Li, Shuyi; He, Xu; Li, Junsheng; Sun, Yiwei; Yi, Yang; Lamikanra, Olusola
Abstract: The potential use of ultraviolet (UV)‐C (254 nm) to extend postharvest shelf life of fresh unprocessed lotus root ( Nelumbo nucifera G.) was determined. UV treatment for 30 and 60 min effectively reduced weight loss, improved moisture, color retention, and soluble solids of samples when stored at 25°C for 15 days. Microbial growth inhibition of UV was evidenced by 1.8 and 1.0 log reductions in the 30 and 60 min‐treated samples. Phenylalanine ammonia lyase (PAL) activity and total phenol contents (TPCs) detected in lotus root were higher, while oxidative enzymes peroxidase (POD) and polyphenol oxidase (PPO) were inhibited by UV treatment. Gallic acid, gallocatechin, and catechin levels were increased in 30 min‐treated samples by about 0.9, 13.4, 8.0 mg/100 g. The results suggest that extension of postharvest storage life by UV‐C is most likely through the protective roles exerted from stimulation of the phenylpropanoid pathway in the treated roots. Practical applications: Unlike previous studies that are mainly focused on shelf life extension of processed products of the rhizome, this study determines the potential use of a nonchemical and ecologically friendly ultraviolet (UV‐C) treatment to extend shelf life of intact uncut fresh lotus root. Our results demonstrated that UV‐C treatment significantly prolonged the shelf life of lotus root. Use of this method is promising as a treatment to improve postharvest storage life of fresh lotus root, to improve its export potential and help to address unmet local demands for the crop. Abstract : UV‐C treatment significantly prolonged the shelf life of fresh lotus root. Treatment of the root preserved key quality parameters such as tuber weight and color and inhibited microbial growth. The UV‐induced prolonged postharvest shelf life appears to be related to the protective roles exerted from stimulation of the phenylpropanoid pathway in the treated roots.